iPSC‐derived NK cells with site‐specific integration of CAR19 and IL24 at the multi‐copy rDNA locus enhanced antitumor activity and proliferation - Yuxuan Zhang; Qingxin Shi; Peiyun Wang; Chujun Huang; Shuqing Tang; Miaojin Zhou; Qian Hu; Lingqian Wu; Desheng Liang (MedComm, 2024)
Abstract The generation of chimeric antigen receptor‐modified natural killer (CAR‐NK) cells using induced pluripotent stem cells (iPSCs) has emerged as one of the paradigms for manufacturing off‐the‐shelf universal immunotherapy. However, there are still some challenges in enhancing the potency, safety, and multiple actions of CAR‐NK cells. Here, iPSCs were site‐specifically integrated at the ribosomal DNA (rDNA) locus with interleukin 24 (IL24) and CD19‐specific chimeric antigen receptor (CAR19), and successfully differentiated into iPSC‐derived NK (iNK) cells, followed by expansion using magnetic beads in vitro. Compared with the CAR19‐iNK cells, IL24 armored CAR19‐iNK (CAR19‐IL24‐iNK) cells showed higher cytotoxic capacity and amplification ability in vitro and inhibited tumor progression more effectively with better survival in a B‐cell acute lymphoblastic leukaemia (B‐ALL) (Nalm‐6 (Luc1))‐bearing mouse model. Interestingly, RNA‐sequencing analysis showed that IL24 may enhance iNK cell function through nuclear factor kappa B (NFκB) pathway‐related genes while exerting a direct effect on tumor cells. This study proved the feasibility and potential of combining IL24 with CAR‐iNK cell therapy, suggesting a novel and promising off‐the‐shelf immunotherapy strategy.